Gender Differences and Lost Flexibility in Online Freelancing During the COVID-19 Pandemic - Dunn, Michael; Munoz, Isabel; Sawyer, Steve (Frontiers in Sociology, 2021)
We report findings from an ongoing panel study of 68 U.S.-based online freelancers, focusing here on their experiences both pre- and in-pandemic. We see online freelancing as providing a window into one future of work: collaborative knowledge work that is paid by the project and mediated by a digital labor platform. The study’s purposive sampling provides for both empirical and conceptual insights into the occupational differences and career plans of freelance workers. The timing of the 2020 data collection provides insight into household changes as a result of the COVID-19 pandemic. Findings make clear these workers are facing diminished work flexibility and increased earning uncertainty. And, data show women are more likely than men to reduce working hours to help absorb the increased share of caregiving and other domestic responsibilities. This raises questions of online freelancing as a viable career path or sustainable source of work.